REFORMASI PENDIDIKAN DI INDONESIA DALAM PERSPEKTIF PENDIDIKAN ISLAM - Burhanuddin Abdullah (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2010)
The article elaborates the educational reform in the perspective of Islamic education. The educational system in Indonesia formulated on the Acts No. 20 of 2003 has underlined how the education is regulated. Precisely, education in Indonesia aims to develop Indonesian man as a whole, both physic and mental aspects. However, the realization of the aim is not all in line with the stated aim. The education in Indonesia seems to have been influenced by Western which is worldly-oriented. In order that the educational aim that is highly glorious can be attained, Islamic education provides an alternative solution toward the problem.